Elections and Embezzlement : Experimental Evidence from Burkina Faso - Lierl, Malte (World Bank, Washington, DC, 2017)
Can democratic elections reduce rent extraction by public decision makers? Existing research suggests that reelection incentives can reduce the embezzlement of public funds. This paper examines three additional mechanisms through which democratic elections could have an impact on embezzlement, even in the absence of reelection incentives: (1) electoral selection effects, (2) social norms and norm enforcement, and (3) citizens' trust in decision makers. Evidence from an experiment with 472 groups of citizens in rural Burkina Faso suggests that electoral selection favors benevolent candidates. Furthermore, elections increase citizens' willingness to punish corrupt decision makers, even if their ability to do so remains unchanged. However, these beneficial effects of elections are offset by an unexpected adverse effect: elections cause citizens to trust decision makers more than they should be trusted. These findings have important implications for the role of information in electoral democracy.